Kajian Literatur: Pengaruh Receivable Turnover dan Working Capital Turnover Terhadap Profitabilitas Perusahaan Manufaktur - Vivian, Angela -; Paramita, Virya Mukti; Meiden, Carmel - (Makro Jurnal Manajemen Dan Kewirausahaan, 2023)
This study aims to describe the development of receivable turnover and working capital turnover on the profitability of manufacturing companies listed on the Indonesia Stock Exchange. This research was conducted on previously published journals, and researchers have collected as many as 30 journals in the form of journals related to the effect of receivable turnover and working capital turnover on the profitability of companies, companies, and or manufacturing companies listed on the Indonesia Stock Exchange. The journals used in this study are journals published in 2012 to 2022. The research technique used is a systematic review of literature or literature study. Literature study itself is a method ofjournaling that collects, reads and records, and processes research materials from previously published journals. The journals for this study were obtained by researchers through thePublish or Perish software. The results show that most of the company's profitability is influenced by working capital turnover and most of the company's profitability is positively influenced by receivable turnover.